Plant biostimulant to improve crops productivity and planters profit. (August 2018) - Santoso, Djoko; Gunawan, A; Budiani, A; Sari, D A; Priyono,
Abstract: Plant biostimulants are applied to meet the challenge for sustainability of agriculture production. IRIBB has developed organic-based biostimulant formulas (OBFs) and tested in the field of several crops. OBF-1 improved the vegetative growth and productivity of some annual food crops. Compared with the control plants, the productivity of OBF-1 treated rice, maize, potato and shallot increased by 25%, 31%, 30% and 23%, respectively. In addition, OBF-1 treated crops indicated more tolerant to pests and diseases. OBFs applications on perennial estate crops demonstrated that OBF-2 and OBF-1 combination increased tea yield around 48% and sugarcane yield up to 50%. Whereas foliar sprays of OBF-3 on oil palm increased the CPO yield by up to 32%. The increased CPO yields were contributed to the increase of total FFB (fresh fruit bunches) weight and oil extraction rate in the fruit mesocarp. OBF-3 is a formula enriched with oil-biosynthetic activators. The farmers and planters should gain additional profits from the increased crop yields in response to the OBF application. How much profits gained were depended also on the price of the commodities. In general, the additional profits were much higher than the OBFs and labour costs.